ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIANKONSUMEN PADA SENTRA PEDAGANG KAKI LIMA(Studi Pada Sentra PKL Babat Jerawat, Pakal-Surabaya) - PRAYUGO, ROBI (Jurnal Pendidikan Tata Niaga (JPTN), 2016)
Centra Street Vendors Tripe Acne stood since 2011, was initiated by the Surabaya city governmentthrough the department of Cooperatives and SMEs and managed by the board LKMK Tripe Acne grow rapidlyuntil today. Existing facilities at PKL Sentra is quite complete from a large parking area, public toilets, andentertainment stage which is held every evening. The purpose of this study was to determine whether thatinfluence purchase decisions on street vendors (study centers pkl tripe acne, pitch-Surabaya) and to investigatewhat factors most influence purchase decisions on street vendors (study centers pkl tripe acne, pitch-surabaya).This type of research is factor analysis using SPSS 18 for windows and technique of factor analysis isconfirmatoring, the following factors which confirmed previous research, among others cultures, price, location,physiological needs, product quality, diversity of products, quality of service, comfort , Mechanical samplingusing quota sampling technique with the number of respondents 100 people. The results of this study are thatinfluence purchase decisions on street vendors (study centers pkl tripe acne, pitch-Surabaya) is influenced bytwo groups of factors: factors physiological needs of the total variance of 42.863% and cultural factors to thetotal variance of 17.052%. Factors in this study that most influence purchase decisions on street vendors (studycenters tripe pkl acne, pitch-Surabaya) is a physiological need factors which consists of physiological needs,comfort, service quality, product diversity. Keywords: factor analysis, culture, price, location, physiological needs, product quality, product diversity,quality of service, comfort